Transformasi Digital Berbasis Etika dalam Pendidikan Islam di Era Kecerdasan Buatan - Muhammad Jailani (Yayasan Literasi Altruis Khatulistiwa, 2025)
Digital transformation in Islamic education during the era of artificial intelligence presents a major challenge in maintaining the balance between technological advancement and spiritual values. This study aims to examine how ethics-based digital transformation can be applied to Islamic education in the era of artificial intelligence (AI), and to identify Islamic ethical principles that can ensure the use of technology is aligned with spiritual and moral values. The research method used is directed case analysis, which focuses on the application of Islamic ethical values ​​in the implementation of educational digitalization in Islamic educational institutions. The results show that the values ​​of trustworthiness, digital honesty, algorithmic fairness, data protection, and digital communication etiquette have become key pillars in guiding the responsible use of technology. The findings also show that Islamic educational institutions that implement these principles tend to have higher levels of ethical digital literacy and are able to anticipate the risks of algorithmic bias and technology misuse. The implications of this research emphasize the need to develop digital ethics guidelines based on the maqasid sharia (the principles of Islamic law), integrate morally oriented digital literacy into the curriculum, and establish a center for the study of technology ethics to ensure that digital transformation not only generates efficiency but also strengthens character, spirituality, and civility in Islamic education